Beyond the empty shelves: Scopes from autoethnography on the consumption of toilet paper in Metropolitan Lima during the COVID-19 pandemic - Armas Gonzales, Marcelo (2021)
In this article, we will analyze the massive purchases of basic products such as toilet paper, as well as the repercussions of these behaviors in society in the current COVID-19 situation, in Lima, Perú. For this purpose, we rely on concepts such as liquid fear, consumer anthropology and crowd psychology, to help us support the following thesis: behind an apparently irrational behavior, there is a cultural apparatus determined by the neoliberal model that promotes the obtaining of material goods as a process of satisfaction and search for unconscious stability on individuals. Likewise, we will use the autoethnographic method to achieve greater involvement with the conclusions derived from the study, mainly those related to the self-perception that these excessive consumption practices generate in others. Following these findings, they confirm the need to address this issue in future research on the COVID-19 situation.